Novel Technologies Based on Supercritical Fluids for the Encapsulation of Food Grade Bioactive Compounds - Stefan Klettenhammer; Giovanna Ferrentino; Ksenia Morozova; Matteo Scampicchio (Foods, 2020)
In recent years, the demand for nutritive, functional and healthy foods has increased. This trend has induced the food industry to investigate novel technologies able to produce ingredients with enhanced functional and physicochemical properties. Among these technologies, one of the most promising is the encapsulation based on supercritical fluids. Thanks to the inherent absence of organic solvent, the low temperature of the process to reach a supercritical state and the capacity to dissolve lipid soluble bioactives, the encapsulation with supercritical carbon dioxide represents a green technology to produce several functional ingredients, with enhanced stability, high load and tailored protection from environmental factors. Furthermore, from the fine-tuning of the process parameters like temperature, pressure and flow rate, the resulting functional ingredient can be easily designed to tailor the controlled release of the bioactive, or to reach specific levels of taste, odor and color. Accordingly, the aim of the present review is to summarize the state of the art of the techniques based on supercritical carbon dioxide for the encapsulation of bioactive compounds of food interest. Pros and cons of such techniques will be highlighted, giving emphasis to their innovative aspects that could be of interest to the food industry.